Answer:
-2
Step-by-step explanation:
-3x - 2x = 8 + 2
-5x = 10
x = -2
2 8 −10−15÷3=2, start superscript, 8, end superscript, minus, 10, minus, 15, divided by, 3, equals
Sergio039 [100]
Answer:
241
Step-by-step explanation:
Given the equation to evaluate :
2^8 −10−15÷3
2^8 = 256
256 - 10 - 15 ÷ 3
From BODMAS principle, we evaluate the divison before subtraction :
-15 ÷ 3 = - 5
256 - 10 -5
256 - 15
= 241
-5 + n is another way to write the expression.
Do what is in the parentheses then add
Answer:
(16x + 21) and (16x - 6)
Step-by-step explanation:
f(g(x)) = f(6 + 4x)
Applying the f(x) function on (6 + 4x) gives
4(6 + 4x) - 3
Which equals 16x + 24 - 3
= 16x + 21
g(f(x)) = g(4x - 3)
Applying the g(x) function on (4x - 3) gives
6 + 4(4x - 3)
Which equals 6 + 16x - 12
= 16x - 6